Catcher Plants - Big Book - Sharon Callen (Bharat Capstone Classroom, 2015)
Catcher Plants highlights five extraordinary plants that catch insects! The text features are photographs, directional arrows, labels, and a picture glossary.
Keywords: Big Book -- Big Book